Application Value of Management Model Based on “Zero Tolerance” Concept in Pressure Ulcer Management - Yufei Liu; Changming Zhou; Nan Li; Xiaoxue Gong (Emergency Medicine International)
Background. Pressure injuries are the most prevalent health problem worldwide. Improving the quality of hospital pressure injury management is an important indicator to improve the quality of hospital management. Objective. To explore the application value of the management model centered on the concept of “zero tolerance” in the management of pressure ulcers (PU). Methods. The effects of conventional management mode and management mode centered on the concept of “zero tolerance” on PU patients and nursing staff were retrospectively analyzed. The patients were evaluated by the general comfort questionnaire (GCQ), Generic Quality of Life Inventory 74 (GQOL-74), and pressure ulcer healing scale (PUSH). At the same time, the satisfaction of PU patients and nursing staff with different management modes was investigated. Results. When comparing the conditions of patients under different management modes, it was found that the “zero tolerance” management mode can improve the comfort and quality of life of patients during hospitalization. Compared with the conventional management mode, the “zero tolerance” management mode can significantly improve the degree of pressure ulcer healing in patients. In addition, the “zero tolerance” management model can not only improve the satisfaction of patients with management but also improve the satisfaction of nursing staff with management. Conclusion. Standardized management of PU patients with the concept of “zero tolerance” as the core can improve the health status and quality of life of patients, promote wound healing, and improve the satisfaction of patients and nurses with the management plan.